The impact of the presence of the ride sharing service "Grabcar" on Metro Manila traffic congestion - Belmonte, Martin Christopher Tongson; Cabanos, Nicholas Ramirez
With today’s rising levels of traffic congestion in Metro Manila, an average 30-minute commute can take nearly double the amount of time. This thesis utilizes Time Series regression to examine the impact of Ride Sharing applications, particularly GrabCar, on the levels of congestion in major roads within Metro Manila. Our traffic congestion measure, which will be further elaborated and explained below, comprises 16 of the major roads in Metro Manila which were measured from the years of 2005 until 2018, a total of 14 years, and other variables that are related to the number of vehicles on the road. This thesis then analyzes the effects of the independent variable, the presence of GrabCar, on the congestion measure. The model presented the observed variables related to population, gas prices, and diesel prices throughout the years in Metro Manila to be the significant explanatory variables in this study. As such, the analysis shows empirically that the presence of GrabCar in Metro Manila had no direct effects, neither positive nor negative, on the level of congestion. We hope that through this thesis, we can begin to extract and pinpoint the main culprits of the worsening congestion level here in Metro Manila.